The relationship between mobile application and job performances of employee at Land and Survey Department Kota Samarahan / Muhammad Azim Norhisham ... [et al.] - Norhisham, Muhammad Azim; Ramli, Fadhilah Aisyah; Sharidan, Syarfieza; Mokhtar, Mardyha (2017)
Job performance refers to the work performance of each worker that shows their attitude towards attaining their objectives (Nadeem, Ahmad, Abdullah, & Hamad, 2014). It is to know what and how the employees are willing to accomplish their work on time by looking at their attitude. Job performance displays the attitude of employee who will complete a task on time, improve their skills, energetic in doing their work and achieve goals to be a productive employee. The performance of the employee can be improved by workers reward, training, career protections and the use of the WhatsApp in organizations (Nadeem et al., 2014). It is because the employees can learn easily through technology and they will be happy and energetic in doing their work. When their emotion is good, they will give their full attention and corporates in completing tasks. Thus, job performance is so important to be highlighted so that employees can learn and improve their skills in order to achieve goals of the organizations. Communication is important to employees so that they can improve their knowledge and achieve the organization's goals together and individually influence the job performance.